2017
DOI: 10.21276/apalm.1547
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological spectrum of Nephrectomy specimen in a tertiary care centre: with an emphasis on Chronic Pyelonephritis

Abstract: the nephrectomy specimen received in the department over a period of three years (January, 2013 to December 2015 were included. A total of 34 cases of nephrectomy specimen were studied during this period.Patients details were noted, which includes age, sex, clinical findings and radiological investigations. This is a retrospective study, so all nephrectomy cases were taken out from the records ABSTRACTIntroduction: Nephrectomy is a common procedure in urological practice done for various conditions like calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…Most common cause is obstructive uropathy due to stricture or calculi, which leads to reflux of the infected urine into the renal pelvis. Calcium oxalate stones are the most common renal calculi seen which occurs due to consumption of hard water and supersaturation of calcium oxalate in the urine [10]. In our study, renal stones were present in two cases and two patients had underlying disseminated tuberculosis.…”
Section: Discussionsupporting
confidence: 45%
“…Most common cause is obstructive uropathy due to stricture or calculi, which leads to reflux of the infected urine into the renal pelvis. Calcium oxalate stones are the most common renal calculi seen which occurs due to consumption of hard water and supersaturation of calcium oxalate in the urine [10]. In our study, renal stones were present in two cases and two patients had underlying disseminated tuberculosis.…”
Section: Discussionsupporting
confidence: 45%
“…In age group of 41-60 years 51-60 years maximum number of cases were found. Kathirvelu S et al [11] are also documented similar observation in their earlier study where they also found in the age group of 51-60 years maximum cases were seen.…”
Section: Discussionsupporting
confidence: 78%
“…This was in concordance with studies by Ashima N Amin (51.6%) and Madhu Kumar et al, (58.33%) and Kulkarni et al [17][18][19] The most common clinical presentation in patients undergoing nephrectomy was found to be flank pain which is consistent with other studies like Aiman et 12,20,24 The incidence of stone( renal and ureteric) was 55% which was much higher as compared to studies done by shanmugasamy. 2 Non neoplastic lesions requiring nephrectomy were more common were males (2:1). This was consistent with studies done by Shanmugasamy et al, Suryawanshi et al 2,14 However some cases of Xanthogranulomatous Pyelonephritis showed a slight female preponderance(1:2) which was similar to studies done by Aiman et al, (1:1.6), Sreedhar et al (1:3), Shaila (100% female).…”
Section: Discussionmentioning
confidence: 99%
“…2 Non neoplastic lesions requiring nephrectomy were more common were males (2:1). This was consistent with studies done by Shanmugasamy et al, Suryawanshi et al 2,14 However some cases of Xanthogranulomatous Pyelonephritis showed a slight female preponderance(1:2) which was similar to studies done by Aiman et al, (1:1.6), Sreedhar et al (1:3), Shaila (100% female). 12,20,25 Malignant tumours (96.4%) compromised most of the renal neoplastic lesions requiring nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation